Case report: Late onset type 3 hemiplegic migraine with permanent neurologic sequelae after attacks - Jokubaitis, Mantas; Lengvenis, Givi; Burnytė, Birutė; Audronytė, Eglė; Ryliškienė, Kristina (Frontiers in Neurology, 2024)
This case study describes a 57-year-old woman with a six-year history of recurrent episodes characterized by visual, sensory, speech disturbances, hemiparesis and severe one-sided headaches accompanied by fever and altered consciousness. Initially misdiagnosed as a stroke, the atypical disease course and MRI findings led to additional genetic testing which revealed a sodium voltage-gated channel gene mutation (T1174S), confirming a diagnosis of sporadic hemiplegic migraine. The migraine prophylaxis showed some improvement in episode frequency and severity. Despite an initial improvement, the patient underwent severe cognitive decline and developed new permanent neurological symptoms during the subsequent 7 years of follow-up.